Analisis Hukum Perdata Pada Perlindungan Hukum Bagi Para Pihak Dalam Kontrak Digital: Studi Kasus Sengketa Saldo DANA - Anami, Mulan Kasisty; Lidowati, Alvina Maretia; Panjaitan, Rachel Netanya; Fadhila, Rasya Aika; Purba, Diana Febri Nauli; S, Surahmad (Media Hukum Indonesia (MHI), 2025)
The rapid development of information technology in the digital era has led to the emergence of digital contracts as agreements conducted through electronic media. Digital contracts share similarities with conventional contracts and are binding to the parties involved as regulated in Article 1320 of the Civil Code, but pose new challenges regarding legal protection for involved parties. This study aims to analyze the legal basis for protection in digital contracts and its practical application. Using a normative juridical method, this research examines regulations such as the Civil Code, ITE Law, Government Regulation No. 71 of 2019, and PDP Law to understand the validity of digital contracts and dispute resolution mechanisms. A case study on DANA balance disputes highlights that while regulations are in place, the implementation of legal protection still requires strengthening. The findings of this study are expected to provide recommendations for enhancing the effectiveness of legal protection in digital contracts in Indonesia.